Competence portfolio assessment of research and development center for regional development - Salminen, Vesa; Kantola, Jussi; Vanharanta, Hannu (Elsevier, 2015)
Digitalization is rapidly increasing and enterprises must find new ways to innovate for business advantage. Engineering industry is currently living in the middle of co-evolution from being the product provider to offering smart services and even to being the provider of customer value. The right way of digitalization can lead to business differentiation by smart services. But to transform themselves, the companies must have the right digital assets, suitable organizational capability and culture, right competence structure and individuals with right mindset to succeed in co- evolution. This article concentrates on analysing the role of research and development unit HAMK Smart Services. Its mission is to support co-evolution of municipal and industrial enterprises as well as value networks and through that increasing the competitiveness of the region. For that purpose, it is important to know the overall capabilities of the HAMK Smart Services unit. In our article we categorize the competence and capability into three layers: human competence and capability, organizational capability and content management capability. This article introduces a new interrelated three layer competence portfolio model and results of survey done with Smart Services research and development unit. Case study analysis has been executed within the customer segment of Industrial digitalization and life cycle care.
Keywords: digitalization; smart services; content knowledge related competence; organization capability; human capability; enterprises; business; know-how; leadership (activity); organisations (systems); learning organisation; cooperation (general); knowledge management; development (active); change; fi=Tuotantotalous|en=Industrial Management|